Correlating Surface Plasmon Resonance Microscopy of Living and Fixated Cells with Electron Microscopy Allows for Investigation of Potential Preparation Artifacts. Issue 6 (28th January 2020) - Kreysing, Eva; Seyock, Silke; Hassani, Hossein; Brauweiler‐Reuters, Elke; Neumann, Elmar; Offenhäusser, Andreas
Abstract: The investigation of the cell–substrate interface is of great importance for a broad spectrum of areas such as biomedical engineering, brain‐chip interfacing, and fundamental research. Due to its unique resolution and the prevalence of instruments, electron microscopy (EM) is used as one of the standard techniques for the analysis of the cell–substrate interface. However, possible artifacts that might be introduced by the required sample preparation have been the subject of speculation for decades. Due to recent advances in surface plasmon resonance microscopy (SPRM), the technique now offers a label‐free alternative for the interface characterization with nanometer resolution in axial direction. In contrast to EM, SPRM studies do not require fixation and can therefore be performed on living cells. Here, a workflow that allows for the quantification of the impact of chemical fixation on the cell–substrate interface is presented. These measurements confirm that chemical fixation preserves the average cell–substrate distances in the majority of studied cells. Furthermore, it is possible to correlate the SPRM measurements with EM images of the cell–substrate interface of the exact same cells, thus identifying regions of good agreement between the two methods and revealing artifacts introduced during further sample preparation. Abstract : This study investigates artifacts at the cell–substrate interface caused by the preparation of cells for electron microscopy. Surface plasmon resonance microscopy (SPRM) measurements in vitro and after chemical fixation confirm that fixation preserves the average cell–substrate distance in neurons. Artifacts introduced during further sample preparation are identified by correlating SPRM measurements and electron microscopy images.